Game on : video game history from pong and pacman to mario, minecraft, and more - Hansen, Dustin, ....- (New York : Square Fish, 2016)
Find out about the fast and furious growth and evolution of video games (including how they are quickly taking over the world!) by looking at some of the most popular, innovative, and influential games ever, from Pong, the very first arcade game, to modern hits like Uncharted. Learn about the creators and inspiration (Mario was named after Nintendo's landlord after he barged into a staff meeting demanding rent), discover historical trivia and Easter eggs (the developers of Halo 2 drank over 24,000 gallons of soda while making the game), and explore the innovations that make each game special (the ghosts in Pac-Man are the first example of AI in a video game). Whether you consider yourself a hard-core gamer or are just curious to see what everyone is talking about, this is the book for you!
Keywords: geschiedenis; video games